2011
DOI: 10.4012/dmj.2010-069
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fatigue testing and cementation mode on the load-bearing capability of bovine incisors restored with crowns and FRC posts

Abstract: The aim of the study was to evaluate the influence of fatigue and cementation mode on the fracture behaviour of endodontically treated bovine incisors restored with fiber-reinforced-composite (FRC) posts and crowns. Forty-eight endodontically treated incisors were restored with FRC posts, composite build-ups, and cast crowns. In 16 teeth, each of the posts were cemented conventionally with KetacCem (3M Espe) or adhesively with Panavia F (Kuraray) or RelyXUniCem (3M Espe). One-half of the specimens in each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
2
6
1
Order By: Relevance
“…The load frequency 6 Hz set in the fatigue test was suggested by a study by Nie et al 19) , who indicated that the 6 Hz test frequency was reasonable when the fiber post was exposed in an air environment to perform fatigue test. The endurance limitation at 1.2×10 6 cycles was 66.81 N for the anatomical SGFR fiber post and 67.77 N for the X-Posts, falling into the reasonable area in previous work ranging from 50-127.4 N 16,28,29) . All failure modes were found in the artificial dentin but not the post itself indicating that post fit adaption in root canal was not a key issue in the lateral resistance test.…”
Section: Discussioncontrasting
confidence: 54%
“…The load frequency 6 Hz set in the fatigue test was suggested by a study by Nie et al 19) , who indicated that the 6 Hz test frequency was reasonable when the fiber post was exposed in an air environment to perform fatigue test. The endurance limitation at 1.2×10 6 cycles was 66.81 N for the anatomical SGFR fiber post and 67.77 N for the X-Posts, falling into the reasonable area in previous work ranging from 50-127.4 N 16,28,29) . All failure modes were found in the artificial dentin but not the post itself indicating that post fit adaption in root canal was not a key issue in the lateral resistance test.…”
Section: Discussioncontrasting
confidence: 54%
“…They found no difference between conventional cementation (Ketac Cem) and adhesive luting (RelyX) with regard to fatigue of FRC posts. Only after inducing fatigue by thermal cycling and chewing simulation was a significant difference in specimen fracture force found in favour of conventional cementation (371 N and 494 N for RelyX and Ketac Cem, respectively) 7. In our study, a favourable outcome for the adhesive luting agent was found.…”
Section: Discussionsupporting
confidence: 38%
“…[ 10 ] Despite the proper fit of the cast posts and cores, their application has been limited due to their solely frictional intracanal retention and their relatively high fracture rate as a factor of their stiffness. [ 11 ] Therefore, there has been a shift toward application of resin-based posts, which offers a closer modulus of elasticity to the root and an adhesive along with mechanical retention, leading to superior stress distribution under functional loads. [ 12 ] The flared root in ECC patients lacks sufficient coronal and apical dentin to gain proper fitness for the prefabricated posts.…”
Section: Discussionmentioning
confidence: 99%